The Role of Tour Guides in Enhancing Tourist Experiences on Talempong Cultural Tourism in West Sumatra - Rina Armeniza Aziz (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
Talempong cultural tourism as a cultural identity of the Minangkabau people. Tour guides play a crucial role in cultural tourism, but empirical research specifically examining the role of guides in the context of Talempong cultural tourism is still limited. This study aims to analyze the role of tour guides in enhancing tourists' experiences on Talempong cultural tourism in West Sumatra. This study uses a qualitative descriptive approach with data collection techniques including in-depth interviews, participant observation, and documentation. The research informants consisted of 12 certified tour guides, 25 domestic and international tourists, and 5 cultural practitioners in West Sumatra. The results revealed that tour guides perform five main roles: cultural interpreters who translate and contextualize the history and philosophy of Talempong music, cultural mediators who bridge the differences in perception between tourists and local culture, experience facilitators who create meaningful interactions between tourists and Talempong artists, identity guardians who ensure the authenticity of Talempong cultural offerings, and co-creators of memorable tourism experiences. This study found that tour guide competencies, particularly cultural knowledge and communication skills, significantly shape tourist satisfaction and create memorable cultural experiences. This contribution enriches the literature on the role of tour guides in intangible cultural heritage tourism and provides practical recommendations for tour guide training programs in West Sumatra.